Procedures for the adoption of the International Financial Reporting Standards for property, plant and equipment in an organisation - Habis Alrawashedh, Nahed; Chaudhary, Asiya; Kamel Alzobi, Mo’taz; Alomary, Mazen (International Journal of Psychosocial Rehabilitation, 2020)
Across the business world, private limited and public listed companies were required to strategically adopt international accounting standards for corporate property, plant, and equipment in standards and interpretations as of January 1, 2005. The transition to these standards offers companies several accounting options and maintains a large number of interpretations. These options and estimates were made either for the purposes of the transition (restatement or not of prior acquisitions, measurement of fixed assets at fair value, treatment of actuarial gains and losses, financial instruments, and cumulative translation differences) or for subsequent years (valuation of fixed assets, classification of leases, capitalization of development costs). As the outcomes of previous reports are usually mixed as to the economic concerns of the strategic adoption of IFRS on organizational property, plant, and equipment, our overall analysis makes a general assumption that there are no simultaneous economic benefits to the preparers and major users of financial data. To this end, we compare different measures of the economic benefits to accountants and users of financial data to analyse the statistical significance of the differences thus calculated. In a second approach, we analyse the factors that explain the presumed profits suggested by the IASB's new theoretical framework, namely the lower cost of capital for companies, ease of analysis and interpretation of financial statements for investors, and improved credit ratings for creditors. This analysis covers 250 companies in Arab countries, but especially in Jordan, from 2013 to 2018.